Growth of quasi-texture in nanostructured magnets with ultra-high coercivity. (15th August 2020) - Zha, Liang; Han, Yuyan; Pi, Li; Luo, Yang; Yu, Dunbo; Han, Li; Xu, Junjie; Yang, Wenyun; Liu, Shunquan; Han, Jingzhi; Wang, Changsheng; Du, Honglin; et al.
Abstract: Controlling the phases and structure of nanostructured rare-earth-based permanent magnets is essential to develop magnets with high performance in clean energy technologies. Importantly, simultaneously controlling the texture and morphology of nano-grains can lead to both high coercivity and high maximum energy product in the nanostructured magnets. Here, we demonstrated the use of electron-beam exposure (EBE) as a rapid heating technique to control the crystallization of the Pr-Fe-B magnet. Due to the effect of the extremely high heating rate, EBE can be adapted to control the phase, grain size, and morphology of the amorphous precursor as well as the texture of Pr-Fe-B nano-grains. A quasi-texture nanostructure with optimal magnetic exchange interactions is thus achieved, leading to a record-high coercivity of 29.1 kOe at room temperature. We further applied the Landau model and Coble-Creep model to explain the positive impact of the EBE on the crystallization and microstructure of the Pr-Fe-B magnet. Graphical abstract: Image, graphical abstract